Fighter Brands and Indian Consumers: A Study of Brand Narratives Using Ad Content Analysis - Kar, Surjit Kumar; Dasgupta, Tina (Indian Journal of Marketing, 2015)
Following the American Marketing Association, ’flanking’ is understood as an indirect strategy aimed at capturing market segments (geographical or consumer groups), whose needs are not being well served by competitors, or when the competitors are unwilling or unable to retaliate. Flanker or fighter brands are mostly second-order brands after the main or flagship brand to have their own identity and deter competitors to introduce lower priced substitutes of the main brand of a company. The entire rationality of the flanking strategy rests on competitive strategies of a company and the intended positioning of a brand from consumer perceptions and behavior. There are many such success stories that are available in marketing literature. For example, Pentium&Celeron from Intel; Pampers&Luvs from P&G; Lays&Cheetos from PepsiCo; Nirma Beauty&Nima Rose from Nirma Limited, and so forth. However, flanker brands have their own set of challenges as far as proper positioning is concerned. If not done properly, it may cannibalize the flagship brand as confirmed in few unsuccessful stories. The current paper discussed different dimensions of consumer perceptions regarding the fighter brand (Nima Rose) vis-Ã -vis the flagship brand (Nirma Beauty) of Nirma. A qualitative ad content analysis (ACA) using qualitative analysis package AQUAD 7.0 was conducted to understand different dimensions of the brands under study. Brand narratives from the audio-visual ad copies were gathered, transcribed, and re-storyed into meaningful frameworks across a comprehensive four dimensional model as suggested by Ringer and Thibodeau (2009) of The Verse Group. Brand stories have meanings and persuasions; however, images and aesthetics have feelings and immersion values embedded in the copies. A logical segregation of these elements from the copies could rightly explain the positioning variables of the brands. This paper explored strategic intent of Nirma for positioning flanker brands in an Indian context through a set of predesigned variables.